ECONOMIC DEVELOPMENT ACCORDING TO ISLAMIC UNDERSTANDING - Nurita, Rindra; Abidah , Nafirotul (ISTISMAR, 2019)
Abstract: Economy is considered as the most important development of global strategy in economic system or a country. Therefore, economic development is the main indicator of public anxiety. Although some of it, development in trade skills, science and knowledge has been obtained, and remains full of other affairs in various countries. The purpose of this analysis is to clarify a trade affair in influencing Muslim trade. This analysis uses an influential theoretical analysis method and the law is closely related to theoretical writings and other references, in the social situation studied, namely the customs and norms that apply. According to the opinion of this analyst, economic development becomes the view of Muslims with regard to traditional Islamic science. It seems that instructions regarding this law are enforced directly or indirectly and written by previous scholars in the Qur'an, As-Sunnah. The specificity of increasing and increasing Islamic trade is seen from a more increasing view of human development that is developed and the strengthening of supporters to maintain one's rank and level. And this does not only take from monetary needs alone, but also from the goal of planning the needs of the afterlife. Keywords: Economic Development, Equality, Welfare, Understanding of Islam.